Tāhlil āl-Insyā’ āl-Thālābi wāl Mā’ānihi fii Surāh Ghāfir - Akhmad Rusydi; Lailatul Qomariyah; Taufiqurrahman; Nida Munirah (Mantiqu Tayr: Journal of Arabic Language, 2024)
In studying the Arabic language, there is balaghah and there is ma'ani. Insya' thalabi of ma'ani is a sentence that requires a request before not asking. The aim is to describe the types of insya' thalabi in Surah Ghafir and their meanings. This research uses a qualitative approach with Library Research, the object of research is 58 Ayat surah Ghafir of Qur’an. The Research results: (1) found 55 words indicating insya' thalabi in 38 verses with 4 types: (a) al-amr (command) in 25 words with 24 words fi'il amar and 1-word fi'il mudhari' connected with lam al-amr; (b) an-nahi (prohibition) in 1 word in the form fi'il mudhari' which connect to lam an-nahiyah; (c) al-istifham (question) on 17 words in the form of alat: al-hamzah, hal, kaifa, min, ma, aina, ayy, anna (meaning of kaifa). 2 words indicate at-tamanni (wishful thinking) with the tools "asa" and "la'alla"; (d) an-nida (call) on 10 words with the "يا" and 3 rabbana words (letter ya, originally: ya rabbana). (2) The meaning of insya' thalabi in Surah Ghafir is that there are 2 original meanings and non-original meanings: the original meaning for al-amr (commandment) is ad-do'a, an-nash wa al-irsyad, al-iltimas, as-sukhriyyah wa at-ta'jiz, al-ihanah, ar-raja', al-irshad, at-ta'jiz, and at-takwin; for an-nahi (prohibition) one word with original meaning is found. For al-istifham (question) that all the meanings were not original is the meanings of at-ta'ajjub wa at-tahdid, at-tamanni, at-taqrir, al-inkar, an-nafi, at-ta'ajjub, at-nafi wa al-inkar, al-inkar at-taubikh al-tihkam, at-taubikh, al-inkar at-taubikh, at-taqrir at-ta'ajjub, and at-taqri' at-taubikh;  For at-tamanni (wishful thinking), an inauthentic meaning is found, namely at-tarajji;  For an-nida (calling) is original and non-original meanings, the non-original meanings is at-tahassur and ad-do'a. Many types of balaghah are used in the Qur'an and have many meanings and purposes in their use. This analysis contributes to the science of Arabic and the love of the Qur'an as a miracle of God.